Partial Purification and Monosaccharide Composition of Polysaccharides of Hypnea Musciformis by GC Analysis (Bangladesh Journal of Scientific and Industrial Research, 2007)
Dried chopped plant of Hypnea musciformis (red algae) was extracted with hot water and cold dilute acid. Yield of High Molecular Weight Crude Polysaccharide HMWCP obtained by ethanol precipitation and lyophilization were in the range of 15-20 %. Anion exchange chromatography of dialyzed material provided a homogenous fraction. Acid hydrolysis and monosaccharide composition were determined as a function of time. Separation achieved by paper chromatography and GC analysis as an alditol acetates showed galactose as a predominant sugar of the polysaccharides. A significant amount of glucose was found in crude sample. Xylose/arabinose and some fucoses were also detected in various proportions in crude and partially purified fractions.Bangladesh J. Sci. Ind. Res. 41(3-4), 141-146, 2006